(untitled) (Economic and Political Thought, 2023)
Hospital-based health technology assessment (HB-HTA) is a growing field with constantly improved methodology. It provides substantial support to hospital management in deciding on medical technologies implementa- tion. HB-HTA specificity requires adequate organization and manage- ment at the hospital level as well as coordination with health technology assessment (HTA) at a national level and the use of the EU’s supporting instruments. The article presents foreign solutions regarding management of HB-HTA units – in the light of the AdHopHTA guiding principles – in six European and North American hospitals, coordination between HB-HTA and health technology assessment (HTA) at the country level – on the example of the Austrian model, and EU regulations and ventures oriented on HTA and HB-HTA development. These issues were developed mainly on the basis of interviews conducted with the heads of HB-HTA units in the surveyed hospitals, with the director of the Austrian HTA Institute (AIHTA), and with the representative of the European Commission. The importance of training HB-HTA specialists, and creating databases and platforms for information exchange and knowledge sharing was particularly underlined in the conclusions and recommendations with regard to HB-HTA development in Poland.